Belajar Investasi Saham untuk Pemula Edukasi Literasi Keuangan Bagi Siswa SMK Pasundan Majalaya - Musadat, Irfan Achmad; Rusnendar, Elan; Pramayuda, Agung (LPPM UNIBI, 2024)
This study aims to enhance students' financial literacy through education on stock investment. The research targets students of SMK Pasundan Majalaya, who are considered to have significant potential to understand investment concepts from an early age. The research method employed is a descriptive qualitative method with a participatory education approach. The educational activities include basic understanding of stocks, the workings of the capital market, risks, and investment strategies for beginners. The results of the study indicate that this education significantly improves students' understanding of stock investments, making them more aware of the importance of financial management and investment as a step toward future financial stability. The implications of this study emphasize the need to integrate financial literacy materials, particularly stock investments, into the vocational high school curriculum. This is expected to prepare students with relevant skills to face global economic challenges.